PRANKVERTISING IN ISLAMIC MARKETING: CASE STUDY OF KEY OPINION LEADER SOCIAL CAMPAIGN - Al Ma’rifatul A’la; Intan Fitranisa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Social media creativity has transformed marketing practices, including in the Muslim market where Islamic marketing ethics are essential. One emerging strategy is prankvertising, which attract public attention through provocative content but may challenge ethical boundaries. While previous studies mainly examined prankvertising through humor and audience perception, this study analyzes it from an Islamic marketing perspective. Using a qualitative single-case instrumental case study, data were collected from social media content and public comments within a specific campaign period and analyzed through thematic coding and triangulation. The findings reveal four phases of the prankvertising campaign: initial trigger, public response, opportunity gimmick, and official advertisement release. Although some phases aligned with the goals of Islamic marketing, significant deviations were found. The trigger content generated polarizing reactions, conflicting with spiritual wisdom and Falah (well-being), while the opportunity gimmick failed to reflect Ihsan (integrity and excellence), highlighting ethical inconsistencies.